Evaluation of the inhibitory activities of thyme compounds against coronavirus disease-19 (COVID-19) by molecular docking and molecular dynamic simulation - Saba Hadidi (Shiraz University of Medical Sciences, 2022)
We have explored the inhibitory capability of Thymus vulgaris compounds against ACE2 protein -the host receptor for SARS-CoV-2, papain-like and main protease of the SARS-CoV-2 through molecular simulations. The docking results showed that the compounds had a greater capability to inhibit ACE2 and papain-like protease in comparison to the main protease. The majority of compounds (61.7%) bind to the S2 active pocket of ACE2. The most powerful anticoronavirus activity is expressed in the order: Terpinolene > Thymol > Bicyclogermacrene. Pi interactions play key roles in the binding of three compounds to the active sites of ACE2 enzyme. 34 out of these 60 compounds were fitted in the PLpro active site. α-humulene followed by (+)-Spathulenol, and (-)-β-Bourbonene showed strong capacity to inhibit PLpro binding site. Except for (+)-Spathulenol which also formed H-bond with Asp165 and Tyr274 amino acids, α-humulene and (-)-β-Bourbonene conjugate with PLpro were stabilized mainly through alkyl and pi interactions. According to the Mpro docking results, 58.3% of thyme compounds could block the active site. The binding energy order was (-)-Spathulenol at highest, then Bicyclogermacrene, (+)-δ-cadinene, (+)-Spathulenol, and Viridiflorol, followed by (-)-β-Caryophyllene oxide. Cys145, His41, Met49, and Met165 are key residues in the interaction of these ligands with the enzyme binding site. The weakest interaction with all three enzymes was observed for (R)-(-)-1-Octen-3-ol and (3S)-Oct-1-en-3-ol. Based on the molecular dynamics simulation lowest conformational change was detected for ACE2 in the present of Terpinolene. (-)-Spathulenol and α-Humulene had the least and most displacement compared to its initial positions, respectively.Please cite this article as: Saba Hadidi. Evaluation of the inhibitory activities of thyme compounds against coronavirus disease-19 (COVID-19) by molecular docking and molecular dynamic simulation. Trends in Pharmaceutical Sciences. 2022;8(2):95-106. doi: 10.30476/TIPS.2022.94389.1137